2012
DOI: 10.1111/j.1472-4642.2012.00938.x
|View full text |Cite
|
Sign up to set email alerts
|

Truly enigmatic declines in terrestrial salamander populations in Great Smoky Mountains National Park

Abstract: Aim Woodland salamanders (genus: Plethodon) declined synchronously across many protected areas in Eastern North America by the mid‐1980s, but no cause was attributed to these declines. We hypothesized that the rapid, synchronous loss of several populations of many species was consistent with the invasive pathogen Batrachochytrium dendrobatidis ( Bd), and we resurveyed historic sites to search for Bd in current populations. Location Great Smoky Mountains National Park. Methods We surveyed 35 sites 2–4 times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 67 publications
1
46
0
Order By: Relevance
“…Declines in populations in terrestrial forest salamanders (Family Plethodontidae: Plethodon) occurred throughout the eastern US in the late 1970s to early 1980s [90], although die-offs were not noted and no definitive cause has been identified. Caruso & Lips [91] resurveyed many of Highton's historic collecting sites and found that occupancy and detection were lower for many species of Plethodon in the Great Smoky Mountain National Park. They resurveyed more species at Highton's historic sites and found that many populations of multiple genera have declined in both occupancy and detection (Caruso et al 2012, unpublished data).…”
Section: (V) Eastern United Statesmentioning
confidence: 99%
“…Declines in populations in terrestrial forest salamanders (Family Plethodontidae: Plethodon) occurred throughout the eastern US in the late 1970s to early 1980s [90], although die-offs were not noted and no definitive cause has been identified. Caruso & Lips [91] resurveyed many of Highton's historic collecting sites and found that occupancy and detection were lower for many species of Plethodon in the Great Smoky Mountain National Park. They resurveyed more species at Highton's historic sites and found that many populations of multiple genera have declined in both occupancy and detection (Caruso et al 2012, unpublished data).…”
Section: (V) Eastern United Statesmentioning
confidence: 99%
“…Chytridiomycosis is currently considered to be caused by a single species of fungus, Batrachochytrium dendrobatidis, which is the only chytridiomycete taxon known to parasitize vertebrate hosts. However, B. dendrobatidis and other factors known to cause amphibian decline fail to explain several recent amphibian population losses (4,5).…”
mentioning
confidence: 99%
“…Given their physiological requirements, they are generally very sensitive to habitat disturbance (deMaynadier and Hunter 1995). Recently, some studies have reported declining abundance of some plethodontid species in North America (Milanovich et al 2010, Caruso and Lips 2013, Kroschel et al 2014, pointing to climate change as a contributing factor for the observed decline. Other studies have predicted negative effects of climate change on the survival of many salamander species in the northeastern United States (Milanovich et al 2010, Sutton et al 2015 as well as on other amphibian species (Parmesan and Yohe 2003).…”
Section: Introductionmentioning
confidence: 99%